(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: Carcinoma of oral tongue has a great potential for metastatic spread to neck nodes, which may not be clinically detected in early stage. To detect frequency of occult neck metastasis in clinically No patients with early oral tongue carcinoma (stage I & II) the study has done. Methods: It was a 2 years cross sectional study among fifty patients in three tertiary care hospitals of Dhaka from 2016 to 2018. Results: Majority of the patients were male (M:F=3:2) with age ranged 25 to 80 years. Among these patients 38(76%) were in T1 and remaining 12(24%) in T2 stage. Tongue ulceration was most common(84%) presenting feature followed by dysphagia(64%) and pain(52%).Only 32(64%) patients revealed no histopathological proved metastasis(true N0). Occult nodal metastasis was significantly common(83.33%) among male patients than females(p<0.01) and also common(72.22%) among < 50 years age group(p<0.01).Sampling node positive was significantly more(66.67%) in T2 stage(p<0.01). Conclusion: Regarding clinical, radiological and histopathological stages and stage migration of early carcinoma in oral tongue this study revealed significant differentiation among these methods. This study implies sampling neck dissection of sentinel neck nodes in early oral tongue carcinoma for management. Bangladesh J Otorhinolaryngol; October 2020; 26(2): 147-152